COMPARATIVE ANALYSIS OF COMMERCIAL BANKS GOVERNMENT OWNED AND PRIVATE BANKS NATIONAL USING RGEC - Yuli Anwar (STIE Binaniaga, 2016)
The global financial crisis that occurred in 2008, the opening of free trade of Southeast Asia (MEA). As well as the use of new methods in the assessment of the health of the bank directly or indirectly impact on the health of the banking performance changes. This study aims to determine the differences between the health levels of government-owned banks and national enterprises listed on the Indonesia Stock Exchange in 2013 and 2014. An assessment of the soundness of banks is an assessment of the factors RGEC the risk profile (risk profile), corporate governance good (good corporate governance), earnings (earnings), and capital (capital). Banks are becoming a sample of 27 banks of the population of 41 banks with purposive sampling method. The data analysis technique used is the Independent sample T-test.The results showed that the condition of banks in terms of risk profile, corporate governance and capital in a healthy state with PK-II both in 2013 and 2014. In terms of profitability shows that state-owned banks in better shape with a very healthy predicate either in 2013 or 2014 . Meanwhile, a national privately owned banks in the state are healthy enough to PK-III both in 2013 and 2014. in addition, the results also showed that there were no differences between the health levels of government-owned banks and national private sector. Partially factor risk profile, corporate governance and capital did not show any significance between the government and private banks nationwide. While the earnings factor show opposite results.Keywords: Health Bank, RGEC, Risk Profile, GCG, Profitability, Capital.